IMPLEMENTATION OF BEHAVIOR MODIFICATION TECHNIQUES FOR PERSON WITH INTELLECTUAL DISABILITY TO INCREASE ACTIVITY OF DAILY LIVING - Tiara Tri Sofiani; Meiti Subardhini; Sinta Yulianti Suyono (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The implementation of behavior modification techniques for persons with intellectual disabilities aims to address specific measurable behaviors that contribute to the improvement of daily living skills (ADLs). An experimental Single-Subject Design (SSD) approach with a quantitative descriptive method, including A-B-A model was used to assess the efficacy of the intervention. The respondent was a persons with intellectual disabilities  who receives services at Sentra Terpadu Kartini Temanggung, selected based on recommendations from a team of social workers, psychologists, and dormitory supervisors. Two primary techniques were applied such as modeling and advice giving and instructions. The ADLs was observed first by ADL Barthel Indeks modification test, with an improvement following treatments. The treatment focused on the low fundamental ADLs and were possitively effective at helping the subject overcome their ability to do the basic lives. The outcomes of this study contribute to the establishment of the utilization of behavior modification skills. It is anticipated that the results could be a reference for practitioners in social rehabilitation efforts to increase the fundamental ADLs of persons with intellectual disabilitis based on their capabilities.